2010
DOI: 10.3989/scimar.2010.74n2395
|View full text |Cite
|
Sign up to set email alerts
|

<i>Pseudo-nitzschia</i> species on the Catalan coast: characterization and contribution to the current knowledge of the distribution of this genus in the Mediterranean Sea

Abstract: SUMMARY: Proliferations of the genus Pseudo-nitzschia recur along the Catalan coast (NW Mediterranean) throughout the year. The establishment of 58 clonal cultures facilitated morphological studies with scanning electron microscopy (SEM) and ITS 5.8S rDNA sequence characterization. Moreover, strains of each species were examined with respect to sexual compatibility and toxicity. The results of the morphological and phylogenetic studies confirmed nine species of the genus Pseudo-nitzschia: P. brasiliana, P. cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 45 publications
5
21
0
1
Order By: Relevance
“…It has recently been reported in the NW Mediterranean, in Catalan waters (Quijano-Scheggia et al, 2005) and has been regarded as a possible case of introduction or range expansion (Quijano-Scheggia et al, 2010). Concerning Greek waters, this species was found only in the Thermaikos Gulf and was detected for the first time in November 2009.…”
Section: Pseudo-nitzschia Brasilianamentioning
confidence: 78%
“…It has recently been reported in the NW Mediterranean, in Catalan waters (Quijano-Scheggia et al, 2005) and has been regarded as a possible case of introduction or range expansion (Quijano-Scheggia et al, 2010). Concerning Greek waters, this species was found only in the Thermaikos Gulf and was detected for the first time in November 2009.…”
Section: Pseudo-nitzschia Brasilianamentioning
confidence: 78%
“…3) are considered producers of DA (according to LUNDHOLM et al 2011). Domoic acid recorded in shellfish could be related to P. cuspidata and P. fraudulenta, as they are known to be DA producers (RHODES et al 1996, RHODES 1998, TRAINER et al 2009, QUIJANO-SCHEGGIA et al 2010. For the other two species, P. subpacifica is not known to be a DA producer while the case of P. Arenysensis requires some clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Among these species, P. dolorosa has never been recognized as a DA producer while P. pseudodelicatissima (MARTIN et al 1990, PAN et al 2001, AMZIL et al 2001, P. multistriata (RHODES et al 2000, SARNO and DAHLMANN 2000, AMATO et al 2010, QUIJANO-SCHEGGIA et al 2010 and P. calliantha (BESIKTEPE et al 2008, ALVAREZ et al 2009, QUIJANO-SCHEGGIA et al 2010 are already known to be DA producers.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, nine species of the genus were identified through the implementation of morphological keys, genetic data, and mating experiments (45,47). Some of these now documented locally are known to be toxigenic (7,8,44,48,51).…”
mentioning
confidence: 99%